Análisis multitemporal de deforestación mediante matrices de transición en el municipio de Floridablanca, Santander (2023)
Deforestation is an especially important environmental problem for humanity today, so its study is required to mitigate it in the short and long term, considering the different variables, whether natural or anthropogenic, that may intervene in its occurrence.